Analysis and examination of models of explanation of process of policy making: an approach to postmodernist paradigm - Ebrahimi, Motahar (2020)
Postmodernity has crossed the boundaries of art and philosophy very quickly, and by challenging the philosophical foundations of the social sciences, it has a great influence on mastering the theorizing of these fields. Consequently, the science of policymaking in general, and theories of policymaking in particular, have not remained immune to postmodern doctrines. Having said this, the objective of this essay is the analysis and examination of the models of explanation of the policy formulation process based on an approach of the postmodern paradigm. To this end, the issues of rationality in postmodernism, rationality in policymaking, and approaches that follow various types of rationality are discussed. The main models for explaining the policy-making process that have drawn much attention from thinkers are outlined. Studies suggest that notions such as objectivity criticism, escaping rationality, superficial, and negation of origin, and notions such as improvement, development, and justice, are among the characteristics of the postmodern paradigm that influence the policy formation ideas. The influence of the aforementioned notions in the policymaking process should be seen as a reminder of issues such as the chaotic model in policymaking, power centers, pressure groups, the mechanism for including marginal and insignificant issues on the agenda, the lack of universal models and insistence on national models of development and public decision-making, pluralism and participation.